Smile Beach murder - Bessette, Alicia (Bessette, Alicia. Outer Banks bookshop mystery, 2022)
"For fans of resourceful amateur sleuths, thriller-leaning cozies, and readers of Jenn McKinlay's Library Lovers Mysteries. From international bestselling author Alicia Bessette comes an all-new mystery series featuring Callie Padget a former reporter turned bookshop clerk in the Outer Banks who is pulled into a deadly web of secrets when a mysterious fall at a lighthouse echoes a tragedy from her past"--